Generation of Soluble NKG2D Ligands: Proteolytic Cleavage, Exosome Secretion and Functional Implications. (21st July 2013) - Chitadze, G.; Bhat, J.; Lettau, M.; Janssen, O.; Kabelitz, D.
Abstract: The activating natural killer group 2 member D (NKG2D) receptor is expressed on NK cells, cytotoxic T cells and additional T cell subsets. Ligands for human NKG2D comprise two groups of MHC class I‐related molecules, the MHC class I chain‐related proteins A and B (MICA/B) and 6 UL16‐binding proteins (ULBP1‐6). While NKG2D ligands are absent from most normal cells, expression is induced upon stress and malignant transformation. In fact, most solid tumours and leukaemia/lymphomas constitutively express at least one NKG2D ligand and thereby are susceptible to NKG2D‐dependent immunosurveillance. However, soluble NKG2D ligands are released from tumour cells and can down‐modulate NKG2D activation as a means of tumour immune escape. In some tumour entities, levels of soluble NKG2D ligands in the serum correlate with tumour progression. NKG2D ligands can be proteolytically shed from the cell surface or liberated from the membrane by phospholipase C in the case of glycosylphosphatidylinositol (GPI)‐anchored molecules. Moreover, NKG2D ligands can be secreted in exosomal microvesicles together with other tumour‐derived molecules. Depending on the specific tumour/immune cell setting, these various forms of soluble and/or exosome‐bound NKG2D ligands can exert multiple effects on NKG2D/NKG2D ligand interactions. In this review, we focus on the role of various proteases in the shedding of human NKG2D ligands from tumour cells and discuss the not completely unanimous reported functional implications of soluble and exosome‐secreted NKG2D ligands for immunosurveillance.